Kappa opioid receptor controls neural stem cell differentiation via a miR‐7a/Pax6 dependent pathway - Xu, Chi; Fan, Wenxiang; Zhang, Ying; Loh, Horace H.; Law, Ping‐Yee (Stem cells (Dayton, Ohio), 2021)
Although the roles of opioid receptors in neurogenesis have been implicated in previous studies, the mechanism by which κ‐opioid receptor (OPRK1) regulates adult neurogenesis remains elusive. We now demonstrate that two agonists of OPRK1, U50,488H and dynorphin A, inhibit adult neurogenesis by hindering neuronal differentiation of mouse hippocampal neural stem cells (NSCs), both in vitro and in vivo. This effect was blocked by nor‐binaltorphimine (nor‐BNI), a specific antagonist of OPRK1. By examining neurogenesis‐related genes, we found that OPRK1 agonists were able to downregulate the expression of Pax6, Neurog2, and NeuroD1 in mouse hippocampal NSCs, in a way that Pax6 regulates the transcription of Neurog2 and Neurod1 by directly interacting with their promoters. Moreover, this effect of OPRK1 was accomplished by inducing expression of miR‐7a, a miRNA that specifically targeted Pax6 by direct interaction with its 3′‐UTR sequence, and thereby decreased the levels of Pax6, Neurog2, and NeuroD1, thus resulted in hindrance of neuronal differentiation of NSCs. Thus, by modulating Pax6/Neurog2/NeuroD1 activities via upregulation of miR‐7a expression, OPRK1 agonists hinder the neuronal differentiation of NSCs and hence inhibit adult neurogenesis in mouse hippocampus. Kappa opioid receptors (OPRK1) promotes the transcription of the stem‐loop miRNA, miR‐7a‐2, through an unknown mechanism. The precursor miR‐7a‐2 in turn generates mature miR‐7a‐5p through processing. The miR‐7a‐5p targets and inhibits Pax6, which facilitates the expression of Neurog2 and NeuroD1, two transcription factors expressed during neuronal differentiation of neural stem cells (NSCs). Overall, OPRK1 controls adult neurogenesis via the miR‐7a/Pax6 pathway.